A matter of life and death – Hunting tactics of Southern elephant seals (Mirounga leonina) and anti-predatory behaviours of their prey - Chevallay, Mathilde; Guinet, Christophe; Goulet, Pauline; Jeanniard Du Dot, Tiphaine (HAL CCSD, 2023)
Abstract For air-breathing marine predators that must save energy during dives, the ability to adopt hunting tactics that minimise the risk of triggering an escape reaction from the prey is crucial for an efficient foraging. Female Southern elephant seals (Mirounga leonina, SES hereafter) forage on small mesopelagic prey that they must hunt almost continuously to meet their high-energy requirements. Here we aimed at understanding how these large time-limited deep-divers can efficiently exploit their small sized prey. To do so, we used data recorded by a new biologger, the sonar tag, deployed on SES during their post-breeding foraging trips. This tag combines an active acoustic sensor with ultra-high-resolution movement and bioluminescence sensors, offering a unique opportunity to simultaneously describe SES’ hunting tactics to capture their prey and defence mechanisms employed by prey. We analysed more than 5,800 prey capture events in nine SES and show that they adopt a “stalking” hunting behaviour allowing them to get as close as possible to their prey before attacking. The ability of SES to adopt stealth approach tactics, minimising the risk of initiating a flight reaction from their prey, might be a key factor in the success of this far-ranging generalist predator.